2018
DOI: 10.1007/s11250-018-1540-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Leptospira serogroup-specific antibodies in cattle associated with reproductive problems in endemic states of India

Abstract: In this study, the seroprevalence and distribution of Leptospira in dairy cattle in endemic states of India were investigated in association with reproductive problems of the cattle. A total of 373 cattle serum samples from 45 farms in Maharashtra, Gujarat, Andhra Pradesh, Telangana, Karnataka, Tamil Nadu, Punjab, Haryana, Chhattisgarh, Sikkim and Uttarakhand states were collected from animals with a history of reproductive disorders like abortion, repeat breeding, anoestrus and endometritis, and also from app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 10 publications
4
33
0
Order By: Relevance
“…In this regard, we already are testing kidneys collected from rodents trapped from several ecological sites, to establish the renal carriage of pathogenic Leptospira and genomic identity of Leptospira species carried by rodents in Uganda. In the present study, we found a high prevalence of anti-Leptospira antibodies against serovar Tarassovi, which has also been reported in cattle (18,23) and pigs (24,25) in East Africa and elsewhere. Though there are not many published reports of leptospirosis in other species of animals in Uganda, we still think that the nature of animal husbandry practices may facilitate interspecies interactions and spread of Leptospira infection.…”
Section: Discussionsupporting
confidence: 83%
“…In this regard, we already are testing kidneys collected from rodents trapped from several ecological sites, to establish the renal carriage of pathogenic Leptospira and genomic identity of Leptospira species carried by rodents in Uganda. In the present study, we found a high prevalence of anti-Leptospira antibodies against serovar Tarassovi, which has also been reported in cattle (18,23) and pigs (24,25) in East Africa and elsewhere. Though there are not many published reports of leptospirosis in other species of animals in Uganda, we still think that the nature of animal husbandry practices may facilitate interspecies interactions and spread of Leptospira infection.…”
Section: Discussionsupporting
confidence: 83%
“…All the serum samples were screened for Leptospira serogroup-specific antibodies by MAT as described earlier at 1:100 dilution [19,20]. A panel of 18 pathogenic reference serovars, namely, Australis, Bankinang, Canicola, Hardjo, Hebdomadis, Tarassovi, Pyrogenes, Icterohaemorrhagiae, Pomona, Shermani, Kaup, Grippotyphosa, Hurstbridge, Javanica, Panama, Djasiman, Copenhageni, and Bataviae was included in the antigen panel while employing MAT [19]. A MAT titer of ≥1:100 was taken as a positive reactor as per the WHO/OIE manual for leptospirosis [20].…”
Section: Methodsmentioning
confidence: 99%
“…(Slavica et al 2010;Andreoli et al 2014;Żmudzki et al 2015). The infections with this pathogen are registered at the present time in many countries including Andaman and Nicobar Islands (Sehgal 2000;Sharma et al 2003;Salgado et al 2015;Chideroli et al 2016;Balamurugan et al 2018;Miyama et al 2018;Sunder et al 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Samples were collected from animals with a history of reproductive disorders like abortion, repeated breeding, anoestrus, and endometritis, and also from apparently healthy animals. The Leptospira antibodies against the serovar hardjo were shown in 27.76% of cattle (Balamurugan et al 2018).…”
Section: Discussionmentioning
confidence: 99%